Rozwiązane

Rozwiąż równania:
b). x^2+4x+3=0
c). 2x^2-7x-4=0
d). 3x^2+5x-2=0



Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

b) x^2 + 4x + 3 = 0

Δ = 4^2  - 4 * 1 * 3 = 16 - 12 = 4

√Δ = √4 = 2

x1 = -4 + 2 / 2 = -2 / 2 = -1

x2 = -4 - 2 / 2 = -6 / 2 = -3

c) 2x^2 - 7x - 4 = 0

Δ = 49 - 4 * 2 * (-4) = 49 + 32 = 81

√Δ = 9

x1 = 7 + 9 / 4 = 16 / 4 = 4

x2 = 7 - 9 / 4 = -2 / 4 = -1/2

d) 3x^2 + 5x - 2 = 0

Δ = 25 - 4 * 3 * (-2) = 25 +24 = 49

√Δ = 7

x1 = -5 + 7 / 6 = 2 / 6 = 1/3

x2 = -5 - 7 / 6 = -12 / 6 = -2